Quantitative analysis of polycyclic aromatic hydrocarbons using high‐performance liquid chromatography‐photodiode array‐high‐resolution mass spectrometric detection platform coupled to electrospray and atmospheric pressure photoionization sources - Hettiyadura, Anusha Priyadarshani Silva; Laskin, Alexander (Journal of mass spectrometry., 2022)
Polycyclic aromatic hydrocarbons (PAHs) are common pollutants present in atmospheric aerosols and other environmental mixtures. They are of particular air quality and human health concerns as many of them are carcinogenic toxins. They also affect absorption of solar radiation by aerosols, therefore contributing to the radiative forcing of climate. For environmental chemistry studies, it is advantageous to quantify PAH components using the same analytical technics that are commonly applied to characterize a broad range of polar analytes present in the same environmental mixtures. Liquid chromatography coupled with photodiode array and high‐resolution mass spectrometric detection (LC‐PDA‐HRMS) is a method of choice for comprehensive characterization of chemical composition and quantification of light absorption properties of individual organic compounds present in the environmental samples. However, quantification of non‐polar PAHs by this method is poorly established because of their imperfect ionization in electrospray ionization (ESI) technique. This tutorial article provides a comprehensive evaluation of the quantitative analysis of 16 priority pollutant PAHs in a standard reference material using the LC–MS platform coupled with the ESI source. Results are further corroborated by the quantitation experiments using an atmospheric pressure photoionization (APPI) method, which is more sensitive for the PAH detection. The basic concepts and step‐by‐step practical guidance for the PAHs quantitative characterization are offered based on the systematic experiments, which include (1) Evaluation effects of different acidification levels by formic acid on the (+)ESI‐MS detection of PAHs. (2) Comparison of detection limits in ESI+ versus APPI+ experiments. (3) Investigation of the PAH fragmentation patterns in MS2 experiments at different collision energies. (4) Calculation of wavelength dependent mass absorption coefficient (MACλ) of the standard mixture and its individual PAHs using LC‐PDA data. (5) Assessment of the minimal injected mass required for accurate quantification of MACλ of the standard mixture and of a multi‐component environmental sample.